Informal Employment and China's Economic Development. Issue 6 (2nd November 2017) - Chen, Ying; Xu, Zhun
Abstract : We measure the size of informal employment using both labor market as well as energy consumption approaches. We find that the share of informal employment in total employment was increasingly most of the time between the mid-1990s and mid-2000s, and started steadily decreasing after that until now. This has two contradicting implications for the Chinese economy. On the one hand, it is good news for China's progress in human development as the process of formalization often brings better income and welfare. On the other hand, for China's capitalism this could be bad news since the labor costs are likely to continue increasing with a decline in the reserve army of labor.